Utilization of Video Tutorials in Learning Procedure Text for Grade X Students Office Management and Business Services - Suhardi, Suhardi; Kurniati, Erisa; Indryani, Indryani (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study aims to analyze the effectiveness of video tutorials as a learning medium for Procedure Text material in English subjects for grade X students of the Office Management and Business Services (MPLB) program at Vocational High Schools (SMK). Procedure Text, which contains systematic steps in completing a task, is closely aligned with the vocational competencies required in administrative and office environments. The research method used is descriptive qualitative supported by literature study and initial classroom observations, accompanied by quantitative descriptive data to strengthen the findings. Literature review was conducted to establish the theoretical basis of audiovisual learning, while classroom observations involved 32 students to identify learning needs and evaluate the use of video tutorials. The results show that 84% of students stated that video tutorials made the learning content easier to understand, 78% became more motivated to participate in classroom activities, and 81% demonstrated improvement in identifying steps and linguistic features of Procedure Text. In addition, classroom engagement increased from 56% to 87% after the use of video tutorials. These findings indicate that video tutorials significantly support contextual learning, strengthen students’ vocational English skills, and increase active participation. The study concludes that video tutorials are an effective and relevant learning medium to improve the quality and outcomes of Procedure Text learning in SMK, especially in the MPLB program.